The tax system incidence on unemployment: a country-specific analysis for the OECD economies - José Ramón Garcia; Héctor Sala (Institute for the Study of Labor (IZA), 2006)
This paper provides a detailed analysis on the incidence of the tax structure on the labor market. To do so it goes beyond the traditional examination of the 'level' effect of the fiscal wedge and considers a 'composition' effect defined as a payroll tax bias (PTB): the proportion of payroll taxes paid by employees with respect to the one paid by firms. We develop a right-to-manage model encompassing different wage bargaining systems and the incidence of different type of taxes. Controlling for demand-side and supply-side determinants of unemployment, we show that the PTB plays a significant role in explaining unemployment in the continental European countries, but not in the Nordic nor the Anglo-Saxon ones. We also show that there is no relationship between the incidence of the PTB and unemployment persistence, even though there is a positive one with respect to the level of the fiscal wedge,
Keywords: E24; E62; 330; unemployment; unemployment persistence; fiscal wedge; payroll tax bias